The Analysis of Higher Order Thinking Skills of Islamic Elementary School Students on Science Subject - Peni Susapti; Muhammad Istiqlal (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThe study aims to analyze the students' higher order thinking skills (HOTS) in Science subjects at Islamic Elementary School in Salatiga, Indonesia. It is descriptive qualitative research. Using the nonprobability sampling with convenience sampling method, this study involved 120 students as the sample. The data were gathered using tests, questionnaires, Focus Group Discussions (FGD), and documentations. The descriptive analysis with percentile formula was used to analyze the data. The results indicated that the students' HOTS abilities were still at the low level. In Low Order Thinking Skills (LOTS) questions category, the students' ability to answer questions ranged from 0.6 to 0.9 (good). In Middle Order Thinking Skills (MOTS) questions category, the index of the students' abilities was 0.35 to 0.65 (the medium category). In HOTS questions category, the index of the studentsâ€™ abilities was 0.075 to 0.45 (the low category). Therefore, it is necessary to make efforts in improving the HOTS ability of Islamic Elementary School students.Keywords: higher order thinking skills, Islamic elementary school students, science subject.Â AbstrakPenelitian ini bertujuan untuk menganalisis keterampilan berpikir tingkat tinggi (HOTS) siswa pada mata pelajaran IPA di Madrasah Ibtidayah Kota Salatiga, Indonesia. Penelitian ini merupakan penelitian deskriptif kuantitatif. Dengan menggunakan nonprobability sampling dengan metode convenience sampling, penelitian ini melibatkan 120 siswa sebagai sampel. Data dikumpulkan dengan menggunakan tes, angket, Focus Group Discussion (FGD), dan dokumentasi. Analisis deskriptif dengan rumus persentil digunakan untuk menganalisis data. Hasil penelitian ini menunjukkan bahwa sebagian besar siswa mempunyai kemampuan HOTS berada pada level rendah. Pada soal kategori LOTS, kemampuan siswa untuk menjawab soal berkisar antara 0,6 sampai dengan 0,9 (baik). Pada kategori soal MOTS, indeks kemampuan siswa adalah 0,35 sd 0,65 (kategori sedang). Pada kategori soal HOTS, indeks kemampuan siswa adalah 0,075 sd 0,45 (kategori rendah). Oleh karena itu perlu dilakukan usaha untuk meningkatkan kemampuan HOTS siswa di Madrasah Ibtidaiyah.Kata kunci: keterampilan berpikir tingkat tinggi, siswa madrasah ibtidaiyah, pelajaran IPA.